Scientific Achievements of the School of Academician Olexandr O. Bogomolets - Klimenko, Ludmila O (Acta Baltica historiae et philosophiae scientiarum, 2016)
This article describes the achievements of the pathophysiological school established by Olexandr Olexandrovych Bogomolets (1881–1946)—a brilliant scientist with a broad scientific outlook, founder of the Institute of Clinical Physiology (now the Bogomolets Institute of Physiology in Kyiv). The contribution of the scientific school can be witnessed in the fields of blood transfusion, immunity, reactivity, endocrinology, oncology, and gerontology. Among Bogomolets’s students were the famous scientists M. M. Syrotynin, R. Ye. Kavets’kyi, M. M. Horiev, Yu. O. Spasokukots’kyi and others.